Dampak Pelaksanaan Kebijakan “Kemenag Sultra Bersahabat” terhadap Penciptaan Kondisi Damai - Rahmad (JURNAL ILMIAH GEMA PERENCANA, 2023)
The Regional Office of the Ministry of Religious Affairs of Southeast Sulawesi Province initiated a quite brilliant movement, namely the “Friendly Southeast Sulawesi Ministry of Religious Affairs Movement”, an initiative from the Regional Office of the Ministry of Religious Affairs of Southeast Sulawesi Province to strengthen and accelerate the implementation of a culture of life that is Clean, Religious, Polite, Harmonious based on Technology. The concept of the "Friendly Southeast Sulawesi Ministry of Religious Affairs" is more applicable and implementable because it was deliberately initiated to describe and translate the vision, mission and priority programs of the Ministry of Religious Affairs of the Republic of Indonesia in realizing a pious, moderate, intelligent and superior society and to outline the Garbarata program for the Southeast Sulawesi Provincial Government through five pillars namely Smart Southeast Sulawesi, Healthy Southeast Sulawesi, Concerned Poverty Southeast Sulawesi, Cultured and Faithful Southeast Sulawesi and Productive Southeast Sulawesi, according to the tasks and functions carried out by the Ministry of Religious Affairs.This research found that in theory and practice, interested parties. In accordance with their role, planners, who in fact are an integral part of the Regional Office of the Ministry of Religion of Southeast Sulawesi Province, must uphold the ethics that guide their behavior to support community participation and responsibility for the interests of the community. As a communicator, planners also need to adhere to natural pragmatic norms in communicating in order to gain public trust and be able to build effective communication.